2016
DOI: 10.1159/000450563
|View full text |Cite
|
Sign up to set email alerts
|

Frailty in Chinese Peritoneal Dialysis Patients: Prevalence and Prognostic Significance

Abstract: Background/Aims: Previous studies showed that frailty is prevalent in both pre-dialysis and dialysis patients. However, the prevalence and prognostic implication of frailty in Chinese peritoneal dialysis (PD) patients remain unknown. Methods: We used a validated questionnaire to determine the Frailty Score of 193 unselected prevalent PD patients. All patients were then followed for 2 years for their need of hospitalization and mortality. Results: Amongst the 193 patients, 134 (69.4%) met the criteria of being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 24 publications
3
44
0
3
Order By: Relevance
“…For example, previous studies found that physical frailty is present in around 35% to 50% of hemodialysis patients [8,32] and over 60% of PD patients [23], which are similar to the prevalence of 62% in our present study. On the other hand, the prevalence of depression and cognitive impairment are considerably lower in our present study than previous ones.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For example, previous studies found that physical frailty is present in around 35% to 50% of hemodialysis patients [8,32] and over 60% of PD patients [23], which are similar to the prevalence of 62% in our present study. On the other hand, the prevalence of depression and cognitive impairment are considerably lower in our present study than previous ones.…”
Section: Discussionsupporting
confidence: 91%
“…After informed consent, physical frailty, depressive symptoms and cognitive function were assessed by standard instruments as described previously [23][24][25]. Briefly, frailty was assessed by an in-house Chinese questionnaire that was validated by our group.…”
Section: Assessment Of Frailty Depression and Cognitive Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Более современные данные, однако, свидетельствуют, что увеличенный эриптоз эритроцитов у пациентов с ХБП способствует восстанавлению продолжительности жизни эритроцитов при кровообращении [24,55,176]. Согласно исследованиям in vitro, уремические токсины, такие как ванадат [109], метилглиоксаль [226], акролеин [22] и сульфат индоксила [117], модифицируют эриптоз.…”
Section: эриптоз как элемент патогенеза анемииunclassified
“…Unfortunately, recurrent peritonitis and progressive peritoneal tissue remodeling, as well as angiogenesis, ultimately leads to utrafiltration failure (UFF), which results in discontinuation of PD therapy. Frail PD patients are more likely to be hospitalized, and they require a long stay for each hospital admission [3]. In developed countries, the proportion of dialysis patients undergoing PD significantly declined in the last 15 years [4].…”
Section: Introductionmentioning
confidence: 99%